Autonomic Dysreflexia following Spinal Cord Injury - Balik, Vladimír; Šulla, Igor (Asian Journal of Neurosurgery, 2022)
Autonomic dysreflexia (AD) is a potentially life-threatening condition of the autonomic nervous system following spinal cord injury at or above T6. One of the most common symptoms is a sudden increase in blood pressure induced by afferent sensory stimulation owing to unmodulated reflex sympathetic hyperactivity. Such episodes of high blood pressure might be associated with a high risk of cerebral or retinal hemorrhage, seizures, heart failure, or pulmonary edema. In-depth knowledge is, therefore, crucial for the proper management of the AD, especially for spine surgeons, who encounter these patients quite often in their clinical practice. Systematical review of the literature dealing with strategies to prevent and manage this challenging condition was done by two independent reviewers. Studies that failed to assess primary (prevention, treatment strategies and management) and secondary outcomes (clinical symptomatology, presentation) were excluded. A bibliographical search revealed 85 eligible studies that provide a variety of preventive and treatment measures for the subjects affected by AD. As these measures are predominantly based on noncontrolled trials, long-term prospectively controlled multicenter studies are warranted to validate these preventive and therapeutic proposals.
Keywords: autonomic dysreflexia; autonomic hyperreflexia; autonomic nervous system; spinal cord injury